Ultrasound findings predict progression to inflammatory arthritis in anti-CCP antibody-positive patients without clinical synovitis. Issue 12 (22nd January 2016) - Nam, Jackie L; Hensor, Elizabeth M A; Hunt, Laura; Conaghan, Philip G; Wakefield, Richard J; Emery, Paul
Abstract : Objectives: To determine whether ultrasound can identify anti-cyclic citrullinated peptide (anti-CCP) antibody-positive patients without clinical synovitis (CS) who progress to inflammatory arthritis (IA). Methods: In a prospective study, anti-CCP-positive patients without CS underwent ultrasound imaging of 32 joints (wrists, metacarpophalangeal joints, proximal interphalangeal joints and metatarsophalangeal joints (MTPs)) and were monitored for the development of IA. Associations between baseline ultrasound findings (grey scale (GS), power Doppler (PD) and erosions) and (1) progression to IA and (2) development of CS within an individual joint were measured. Results: Consecutive anti-CCP-positive patients (n=136; mean age 51 years, 100 women) were followed up for median of 18.3 months (range 0.1–79.6). At baseline 96% had GS, 30% had PD and 21% had one or more erosions. IA developed in 57 patients (42%) after median of 8.6 months (range 0.1–52.4). Ultrasound abnormalities (GS ≥2, PD ≥1 or erosion ≥1) were found in 86% at baseline compared with 67% of non-progressors (χ 2 =6.3, p=0.012). Progression to IA was significantly higher in those with ultrasound findings in any joint (excluding MTPs for GS) (GS ≥2: 55% vs 24%, HR (95% CI) 2.3 (1.0 to 4.9), p=0.038; PD ≥2: 75% vs 32%, 3.7 (2.0 to 6.9), p<0.001 and erosion ≥1: 71% vs 34%, 2.9 (1.7 to 5.1), p<0.001). Furthermore, progression occurred earlier with PD ≥2 (median 7.1 vs 52.4 months) and erosion ≥1 (15.4 vs 46.5). At the individual joint level, the trend for progression to CS was more significant for GS and PD (GS ≥2: 26% vs 3%, 9.4 (5.1 to 17.5), p<0.001; PD ≥2: 55% vs 4%, 31.3 (15.6 to 62.9), p<0.001). Conclusion: Ultrasound features of joint inflammation may be detected in anti-CCP-positive patients without CS. Ultrasound findings predict progression (and rate of progression) to IA, with the risk of progression highest in those with PD signal. Trial registration number: NCT02012764; Results.